Impact of SOFA Score on The Outcomes of Traumatic Patient in Intensive Care Unit - Gomaa Gomaa; Mostafa Aboelenin; Yousry Abdelsalam (International Journal of Medical Arts, 2023)
Background: When a patient is admitted to the intensive care unit [ICU], organ dysfunction is thought to be the primary cause of death and complications. Since its development in the 1990s, the sequential organ failure assessment [SOFA] score has been used in critical care to assess and forecast acute morbidities and related patient outcomes.The Aim of the work: For assessment SOFA score ability as a diagnostic indicator in predicting traumatic patients’ outcome in the ICU.Patients and Methods: This was a prospective cross-sectional study conducted on all trauma patients who admitted to ICU at Damietta Al-Azhar University Hospital. After approval of ethical committee 70 patients of them ranged from 18 to 69 years were selected.Results: Regarding the cause of admission in the studied population, 24% was abdominal trauma followed by ICH in 20%, multiple fracture in 17.1%, subdural hematoma and pneumothorax in 14.29% for each then Brain contusion in 10% of included patients. The duration of hospital stay ranged between 4-20 days with mean duration of 9.600 ± 4.095 days. SOFA score has sensitivity of 91.7% and specificity of 100% for predicting mortality, at cutoff point 5.5. There was statistical significance positive correlation between SOFA score and the duration of hospital stay.Conclusion: There is statistically significant positive correlation between SOFA score and the duration of hospital stay so It is suggested that SOFA score be used as a suitable tool to predict patients’ outcomes.